PEMURNIAN ETANOL HASIL FERMENTASI KULIT UMBI SINGKONG (Manihot Utilissima Pohl) DARI LIMBAH INDUSTRI KERUPUK SANJAI DI KOTA BUKITTINGGI BERDASARKAN SUHU DAN WAKTU DESTILASI - Marjoni, Mhd. Riza (Universitas Ahmad Dahlan, 2014)
Bukittinggi city with approximately 132 industry crackers Sanjai spend 300-500 kg ofcassava per day for each industry. Solid waste production process results Sanjai crackers thisone is skin cassava. Cassavaâs peel produces 15-20% carbohydrate content of 68-85% of theweight of the bulb, so it has great potential to be converted into bioethanol.Carbohydrates in the tuber peel can be processed into ethanol by fermentation and for separatingethanol from itâs mixture used method of distillation. Distillation temperature and time used affects the quality and quantity of bioethanol produced. This study aims to determine the besttime and temperature distillation to produce bioethanol at the highest levels. Ethanol contentanalysis was conducted using the specific gravity using line arregression equation and Tablegravity of Indonesian Pharmacopoeia. The results showed that the highest levels of ethanoldistillate obtained in the distillation temperature of 71o C for 5 hours is 16.60% using regressionmethods and 14.1% according to Table Pharmacopoeia with yield ranging between 2.30%-5.80% and the efficiency of distillation 28, 94% -57.50%. Time and temperature distillationhave a real impact on the levels of ethanol produced atthe level of 5%.